Interactions between communities improve the resilience of multicultural societies - Jayles, Bertrand (2023)
Previous work by the same authors showed that favoring openness, trust and cohesion within homogeneous communities strengthens their resilience. Here, we extend the social networks model developed there, and study the resilience of a society composed of two communities with different properties. We find that societies with more disparate communities are less resilient, while encouraging communication between communities strongly improves the resilience of the whole.